PRODUKSI DAN KANDUNGAN NUTRIEN HIJAUAN PADANG PENGGEMBALAAN ALAM DI KECAMATAN LORE UTARA, KABUPATEN POSO - Damry Damry (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
A research was performed to study production and nutrient composition of forage produced from a natural grassland in Lore Utara Subdistrict, Poso District. Forage samples were collected from two villages (Winowanga and Alitupu) with a destructive sampling method using a pair of 1 m2 sized quadrant. These samples were then taken to University of Tadulako for dry matter and main nutrient analysis at the Animal Nutrition Laboratory, Animal Science Department. On the basis of dry matter contents, the available dry matter production and carrying capacity were calculated with some assumptions, and all data were descriptically analysed. Results showed that the forage consisted mainly of grass with an average available dry matter production of 941 kg/ha. Average carrying capacity was 0.63 AU/ha/year, calculated assuming 1 AU is equivalent to a 500 kg cattle. Average nutrient contents (g per 100 g) were 6.47 (crude protein), 2.23 (crude fat), 42.71 (crude fibre), 9.98 (ash), and 40.29 (nitrogen free extracts).